FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA ANAK USIA 6-24 BULAN - M Rizal Permadi; Diffah Hanim; Kusnandar Kusnandar (Poltekkes Kemenkes Mataram, 2021)
Background : Prevalence, of stunting, under five years in Boyolali Regency was 28%. Stunting caused by breastfeeding pattern, inadequate intake of energy, carbohydrate, fat, protein, parental height and economic level. Objectives : This objective of this, research, is to analyze, the correlation of the energy, carbohydrate, fat, protein, parental height and economic level intake to the stunting in Boyolali Regency Method : This, research, design, used a cross-sectional approach. Subjects aged 6-24 months who were stunting in this study were 33 children, 77 children were not stunted, data was tested chi-square. Results : The correlation of Breasfeeding pattern, dietary intake of energy, carbohydrates, parental height were significant, correlation with, stunted as indicated, by the p-value <0.05. There was no correlation intake of fat, protein anda economic level with stunted as indicated, by the, p-value, >0.05 Conclusion : Dietary intake of energy, carbohydrate, breastfeeding pattern, and parental height, had correlation with the stunting child.